THE INVESTIGATION OF CULTURE-INTEGRATED MATHEMATICS REMEDIAL MODULES ON INDIGENOUS STUDENTS’ LEARNING OUTCOME: Received: 11th April 2023; Revised: 1st August 2023, 22nd August 2023; Accepted: 26th August 2023 - Lo, Ting-Ying (PUPIL: International Journal of Teaching, Education and Learning, 2023)
The purpose of this study was to use activity theory to analyze the mathematics difficulties of indigenous low-achieving students, to develop culturally integrated mathematics remedial modules to solve this difficulty and test the student's learning outcomes. This research applied the case study method and invited twelve grade 4-5 Truku indigenous students as the participants. The research tools used for analysis included a teacher-student interview outline, an indigenous culture integration mathematics remedial teaching module, classroom videos, and reflection logs. The results showed that the difficulties of indigenous low-achieving students were among the tools, community, rule, and division of labor by activity theory analysis, which caused them to produce contradictory emotions towards mathematics. In the second stage, the study team developed an indigenous culture integrated into the mathematics remedial module to solve the difficulties. After teaching, 70% of the indigenous low-achieving students improved their math performance. The cultural dual-guidance teaching strategy expanded the indigenous students' ability to use multiple representations to solve problems, promoted confidence to present their solving method, and showed the ability to contribute to the group.